Internal Ring Defect Closure Technique in Laparoscopic Mesh Hernioplasty for Indirect Inguinal Hernia - Li, Binggen; Shi, Shange; Qin, Changfu; Yu, Jiwei; Gong, Duhui; Nie, Xiangyang; Miao, Jinchao; Lai, Zeru; Cui, Wenbo; Li, Guoxin (Frontiers in Surgery, 2022)
Purpose: The best way to reduce seroma formation after laparoscopic indirect hernia repair is debated. We noticed that internal ring defect closure in laparoscopic mesh hernioplasty could provide promising outcomes with an effect on diminishing seroma formation. We introduce our closure technique and report our experience. Methods: This prospective study was conducted from May 2019 to May 2021. Patients with European Hernia Society classification L3 indirect or scrotal hernia were recruited and underwent laparoscopic transabdominal patch plasty (TAPP). Hernia defect closure was performed before mesh deployment. The primary outcomes were seroma formation, postoperative pain, and hernia recurrence. Perioperative data and postoperative complications were also recorded. Results: Consecutive 77 patients with 89 indirect hernias (including 51 scrotal hernias) were recruited in two regional tertiary hospitals. All operations were successful without open conversion. The mean size of the hernia defect was 3.7 ± 0.5 cm (range, 2.5–5.0 cm). The mean operative time for each hernia repair (peritoneum to peritoneum) was 48.3 ± 10.8 min (range, 33–72 min), and the mean time required for internal ring closure was 6.7 ± 2.2 min (range, 4–10 min). Intraoperative bleeding was minimal. The mean visual analog scale pain score at rest on the first postoperative day was 2.2 (range, 1–4). The average postoperative length of hospital stay was 18 hours (range, 14–46 h). During a mean follow-up period of 9.4 months (range, 3–23 months), no hernia recurrence or chronic pain was noted. Seroma formation was detected on six sides of unilateral hernia (6.7%) on postoperative day 7, with a mean volume of 45.8 ml (range, 24–80 ml). All seromas were mild and resolved spontaneously within three months, with no need for evacuation or other treatment and without major impact on the final outcome. Conclusions: Defect closure in laparoscopic mesh hernioplasty for large indirect hernias is safe and feasible and can significantly reduce postoperative seroma formation and relative complications. This approach is recommended in large indirect or scrotal hernia repair.